Las Cortes castellano-leonesas del siglo XV en sus documentos: El Registro o Libro de Cortes (1425-1502) - Olivera Serrano, César (Historia del Derecho, 2022)
The manuscript 9/1784 of the Library of the Real Academia de la Historia (Royal Academy of History), known as Registro de Cortes or Libro de Cortes (Registry of Parliament/Book of Parliament), contains a collection of simple copies made by the court scribes and lawyers of the Castilian Cortes (Parliament) at the beginning of the 16th century, in which numerous documents for internal use from the time of John II of Castile, Henry IV of Castile and the Catholic Monarchs were collected. Its time span covers the period between 1425 and 1502. The Registry's texts allow us to understand the operation of the parliamentary institution in numerous matters that are not included in the ordenamientos (ordinances) and the cuadernos de peticiones (notebooks of petitions) published by the Academy itself in the mid-19th century. Although the scientific community was familiar with some of the parts already published, a complete edition of the manuscript was missing, along with an explanation of the meaning of its use in the courtly context, the question of authorship and the characteristics of the copied texts, not to mention the identification of the main actors who played a leading role in that representative assembly. In short, the Registry illustrates the course of the Castilian Cortes in the political framework of its time.